Trends in research on learning in virtual environments, a bibliometric study - Torres-Zamudio, Marleny (Revista General de Información y Documentación, 2025)
The introduction of the technological component in training processes arouses the interest of scientists from different areas, giving rise to a broad and well-founded theoretical spectrum of learning processes under virtual environments. The study seeks to analyze the development and perspectives of learning under virtual environments. In the methodological development, bibliometrics is applied as a useful discipline in the quantitative analysis of scientific documents, using sources and tools such as Scopus, Excel and VOSviewer software. A total of 1,867 documents published between 1996 and 2023 are analyzed, identifying the most cited publications and authors, the countries or territories leading the research, as well as the journals and topics of greatest interest. The bibliometric analysis helps to establish trends and future research agenda. The findings indicate that research on learning in virtual environments is oriented towards four foci: virtual reality, the human being, e-learning and learning systems. Emerging research topics include immersive virtual reality, machine learning, gamification, learning algorithms, virtual simulation, computational thinking and digital learning strategies, and research aimed at making learning more accessible and meaningful in virtual environments.